bm42400
contestada

Janet wants to solve the equation above, what should she multiply by both sides of this equation by

Janet wants to solve the equation above what should she multiply by both sides of this equation by class=

Respuesta :

Answer:

y^2 - 1.

Step-by-step explanation:

We multiply by the Lowest Common Denominator of y + 1 and y^2 - 1 which is y^2 - 1.  (Note y^2 - 1 = (y - 1)(y + 1) ).

For this case, we must bear in mind that:

[tex]y ^ 2-1 = (y + 1) (y-1)[/tex]

So, if we multiply both sides of the equation by [tex]y ^ 2-1[/tex] we have:

[tex]y (y ^ 2-1) + y ^ 2-5 = \frac {(y ^ 2 + y + 2) (y ^ 2-1)} {y + 1}\\y (y ^ 2-1) + y ^ 2-5 = \frac {(y ^ 2 + y + 2) (y + 1) (y-1)} {y + 1}\\y (y ^ 2-1) + y ^ 2-5 = (y ^ 2 + y + 2) (y-1)[/tex]

Thus, we must multiply by:

[tex]y^ 2-1[/tex]

Answer:

[tex]y ^ 2-1[/tex]

ACCESS MORE